2020
DOI: 10.1093/cid/ciaa602
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Natural History of Pulmonary Tuberculosis: A Bayesian Estimation of Natural Recovery and Mortality Rates

Abstract: Background Tuberculosis (TB) natural history remains poorly characterised and new investigations are impossible as it would be unethical to follow up TB patients without treatment. Methods We considered the reports identified in a previous systematic review of studies from the pre-chemotherapy era, and extracted detailed data on mortality over time. We used a Bayesian framework to estimate the rates of TB-induced mortality an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 14 publications
2
37
4
Order By: Relevance
“…Whilst the parameters were estimated by fitting to the data and a two year infectious disease duration, our model matched empirical estimates of cumulative 10-year mortality for all infectious TB of around 40%. 18,21 We also extracted duration of symptoms before treatment. Systematic reviews of self-reported sypmtoom duration usually cite between one and three months of symptoms prior to treatment, whereas we found a median of four months.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the parameters were estimated by fitting to the data and a two year infectious disease duration, our model matched empirical estimates of cumulative 10-year mortality for all infectious TB of around 40%. 18,21 We also extracted duration of symptoms before treatment. Systematic reviews of self-reported sypmtoom duration usually cite between one and three months of symptoms prior to treatment, whereas we found a median of four months.…”
Section: Discussionmentioning
confidence: 99%
“…We used programmatic data to inform the simulated detection and treatment processes and previously published estimates to inform the natural history of TB, 17 as well as the rates of progression from latent to active TB. 16 Model parameters were fitted to local data on population size, TB prevalence, LTBI prevalence and TB notifications using an adaptive Metropolis algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…Our previously published estimates were used to inform the natural history of TB (14), and the progression rates from latent to active TB (13). We fitted model parameters using local data on population size, TB prevalence, LTBI prevalence and TB notifications while considering uncertainty around the most critical model parameters (Table 2).…”
Section: Tuberculosis Modelmentioning
confidence: 99%
“…In this regard, we have introduced the protection factor p, which determines the percentage of active cases that show a smear negative course. The annual spontaneous cure ( '( and ') ) and dying (ÎŒTB,SP and ÎŒTB,SN) rates depend on the SP or SN nature of the disease and is given by Ragonnet et al 33 .…”
Section: 1-tbspectr Modelmentioning
confidence: 99%
“…Recent data based on a precise determination of mortality and curation in the natural history of TB in the pre-chemotherapy era oblige us to modify this model. In this work, the authors have been able to better distinguish the prognostic of sputum positive (SP) and sputum negative (SN) patients, as a sign of TB severity 33 . This data shows a dramatic difference between both forms and allows us to better explore the trade-offs that made this coevolution possible.…”
Section: -Introductionmentioning
confidence: 99%